Energy consumption, economic growth, trade and financial development nexus in South Asia - Hafiz Muhammad Abubakar Siddique; Muhammad Tariq Majeed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
This study contributes to the literature by exploring the impact of energy consumption, trade and financial development on growth in five South Asian countries over 1980-2010. The panel co-integration approach is employed to examine the long run association and granger causality analysis for direction. The PMG estimation approach is used to address the problem of heterogeneity. Panel co-integration test expresses a long run relationship between growth, energy, trade and financial development. Our findings express that financial development, energy and trade positively affect the economic growth. In long run, bidirectional relationship exists among growth and energy, unidirectional causality is running from trade and financial development to growth.
Keywords: 330; Economic growth; Energy consumption; South Asia